Presidents and parties in Latin America: the exceptionality of peronism in the Latin American context - Scherlis, Gerardo (2013)
Political parties have ceased fulfilling substantial representative functions. Their legitimacy lies now on their role as governmental agencies. This led to an increasing interpenetration between parties and the states, and to the empowerment of those leaders that occupy executive offices. In the Latin American context these features are particularly intense in the case of ruling parties in countries where traditional parties collapsed or suffered significant brand dilution. In these cases the president controls the ruling party, while the «really existent» party organization is built up on the basis of networks recruited by the elected leader to run the government. The central argument of this article is that Peronism is the sole political force which has managed to adapt successfully to the conditions of electoral competition in contemporary Argentina. The president´s autonomy in terms of public policies´ in relation to a political machine sustained on the basis of the control of sub-national states makes it possible to disentangle the legitimacy of the party from that of its current national leadership. This scheme provides Peronism with a successful self-preservation mechanism, which is exceptional in the Latin American context.